EFFECT OF STRUCTURE FORMATION UNDER THE INFLUENCE OF HOMOGENEOUS SYSTEMS IN MIDWIFE SANDS - Ахмаджонов И.Л.; Ганибоева Х. Ш. (Galaxy International Interdisciplinary Research Journal, 2023)
Under the influence of the composition of lime and surfactant additives in the sand dispersion, physicochemical processes occur, leading to a change in the morphology of particles and dispersed hardening and, as a result, to the formation of strong aggregates. The possibility of forming a water-resistant structure in a salty sand dispersion using complex reagents combining finely dispersed mineral lime and surfactants, providing the effect of dispersion hardening, has been revealed.